The role of stakeholders in revitalizing religious affairs offices (KUA) for bureaucratic reform in public services: Perspective for sustainable development goals - Samsudin, Sarip Sahrul (Social, Ecology, Economy for Sustainable Development Goals Journal, 2025)
Background: Community service at the Office of Religious Affairs/Kantor Urusan Agama (KUA) is a service that has received a lot of correction from the people in West Nusa Tenggara Province. In this regard, KUA services will be improved by using KUA revitalization. However, the implementation of KUA revitalization had many obstacles that could not be resolved in a short time. The purpose of this analysis is to evaluate and develop the KUA revitalization program in West Nusa Tenggara Province. Methods: This analysis was carried out using a qualitative approach, data analysis was carried out using a descriptive approach. Findings: The results of the analysis are as follows: 1) The KUA revitalization program is not only an Islamic Community Guidance program but a collaboration work around Ministry of Religious Affair and all KUA stakeholder. 2) KUA revitalization is not only a change in mindset and culture set but also need contribution from  agent of change. 3) The main changes in KUA revitalization are changes in human resources. 4) Improvement of infrastructure facilities is carried out based on the priority scale of KUA conditions. 5) It is necessary to change the linear rules with the KUA revitalization program, especially the rules related to SBSN so that they can work together to accelerate the KUA revitalization progress. Conclusion: The KUA revitalization program will be successful if there is cooperation from all work units within the Ministry of Religion. Novelty/Originality of this article: This study offers a unique contribution by highlighting the complex interplay between organizational change, stakeholder collaboration, and regulatory alignment in the context of KUA revitalization, a topic that has not been widely studied in previous research.